Capacity-building model for nurses in carrying out family-based health service at selected primary care units in Northern Thailand - Jitnatee Kaney Ritchie (2018)
The process of using a family-based health service is one that can strengthen and develop primary care services. Nurses, as key professionals in primary care services, are expected to provide care that focuses on families in community settings. This study intended to achieve a change in practice in primary care units regarding family-based health service. Participatory action research using an enhancement approach was utilized as the study methodology. Participants were seven nurses from two primary care unit networks, eighteen primary care unit staff, twenty-five volunteers, five community leaders, fifty-three families and public health administrators, public health technical officers, nurses from other units, and local organization administrators. Data were collected through focus group discussions, interviews, participant observation, document survey and keeping a research journal. Throughout research processes, participants were facilitated and encouraged to develop, to implement and to evaluate their nursing practice, based on the evidence gathered during the study. Strategies to empower nurses and maintain a family-based health service were: 1) partnership, 2) commitment, 3) building capacity, 4) debriefing meetings, 5) communication and mutual learning, and 6) participation in community activities. The study suggests that developing family-based health service is a shared responsibility amongst health care providers, local community organizations, communities and families with nurses at the center of this collaboration and the first point of contact.